Aplicações de controle em processos industriais utilizando lógica fuzzy e FCM/DCN - Matsumoto, Douglas Eidi (2014)
This work presents applications of industrial process control using computational intelligent systems. Among these techniques, the objective is to use fuzzy logic and concept originated from cognitive maps, emphasizing the fuzzy cognitive map and its evolution to a dynamic cognitive network. Two cases of industrial process are analyzed for the control design. In the first case, it is presented two evolutions of FCM, the first works like event driven that switches the sets, the second is the Hebbian learning methods for FCM. Some of the codes generated are embedded in a microcontroller electronic platform (Arduino). For the second case, it is implemented only the fuzzy logic in the plant operating on different conditions. The intention of this work is to show applications of intelligent systems in industrial processes demonstrating and comparing the use of the methods previously mentioned.